2008
DOI: 10.1007/s00417-008-0956-7
|View full text |Cite
|
Sign up to set email alerts
|

Toy gun ocular injuries associated with festive holidays in Kuwait

Abstract: Eye trauma with toy guns resulted in significant injuries that required medical intervention and hospitalization for variable lengths of time, with a potential of causing long-term ocular complications. Our findings should assist public health workers in formulating specific prevention strategies, including a health educational program to make parents and health care professionals aware of the potential harm of these toys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
9
3
Order By: Relevance
“…The results of this current study are similar to previously studies in other countries, which showed that male children below the age of 10 years were predominant [8], [10], [25], [28], [31], [37], [49]. This could be interpreted on the basis that primary schoolchildren are more susceptible than the preschool-aged group, although they are still relatively immature, these children are slightly more independent which may make them more vulnerable [18][22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this current study are similar to previously studies in other countries, which showed that male children below the age of 10 years were predominant [8], [10], [25], [28], [31], [37], [49]. This could be interpreted on the basis that primary schoolchildren are more susceptible than the preschool-aged group, although they are still relatively immature, these children are slightly more independent which may make them more vulnerable [18][22].…”
Section: Discussionsupporting
confidence: 90%
“…Despite of the dissimilarity in medical level, the longer stay might be mainly due to a high number of ocular wall repair in our study (38.1%, 394/1018), which are more serious and costly. The mean length of stay for closed globe wounds per hospitalization was 7.3 days, which is also longer than the stays reported in Kuwait (3.6 days) [31]. These results indicate that ocular trauma causes a significant burden of ophthalmic disease in this region.…”
Section: Discussionmentioning
confidence: 56%
“…In Yemen, injuries attributed to toy guns and fireworks are main reasons for emergency admission to the hospital, especially during the Eid holiday season. Toy guns or airsoft guns shoot small, hard plastic pellets using air pressure or a spring mechanism similar to that of real machine guns and are usually manufactured and imported from China [13]. The air pressure may be compressed by a powerful spring or by repetitive pumping of air into a gas chamber.…”
Section: Original Articlementioning
confidence: 99%
“…The low occurrence of sports injuries in our population suggest the low priority given to sports, and this may be due to poor information about its benefits. In recent studies from developed countries, Sports related injuries have become the most common in adults [40][41][42].…”
Section: Discussionmentioning
confidence: 99%